STRUCTURING SPANISH LEXICON WITH SEMANTIC CLASSES - Blanco, Xavier (Verbum, 2015)
In this paper, we present the hierarchy of semantic labels for Spanish that we are building in the frame of the research project FFI2013-44185-P Semantic labels hierarchy for the genus proximum (next kind) of lexicographic definition (UAB). We describe the notions of semantic label and the notion of actantial formula. The semantic label constitutes the syntactic head of the entry’s formal definition. It must be noted that the definiendum almost never corresponds with the entry form (the lemma) but with a propositional form or actant structure (actantial formula) that includes all the semantic actants of the lemma. Semantic labels are actual linguistic signs of Spanish and not a metalinguistic device. This implies that the regular semantic, syntactic and restricted lexical cooccurrence of a given label with the definiendum can and must be controlled before attributing a lemma to it. This control plays a key role in the elaboration of the hierarchy as it is the central criterion for the attribution of a label. Moreover, it is a distinctive trait of our hierarchy since most sets of semantic labels are made up of metalinguistic entities. Labelling in this way we obtain both a minimal paraphrase of the lemma’s signified and a syntactical substitute in any context. It is worth emphasising that our hierarchy of semantic labels is language-dependent. As a result, it cannot be directly used for translation or for multilingual search operations. However, different mechanisms of connections or equivalences between hierarchies can be proposed in order to consider translinguistic applications. We discuss also several mechanisms of semantic description, as the inclusive disjunction, the exclusive disjunction or the fission of variables. One of the questions that we need to address in the future is how to adapt our hierarchy to label not only the nouns but the other parts of speech as well. We illustrate our comments with Spanish examples accompanied with French translations.